SHIFTING CULTIVATION MODEL: AN ENVIRONMENTAL AND SUSTAINABLE AGRICULTURAL MANAGEMENT PRACTICE - Kristian, Kristian; Harahab, Nuddin; Hakim, Abdul; batoro, jati (Archives of Business Research, 2019)
Shifting cultivation is a cultural wisdom of Dayak people which is considered capable of preserving environmental resources. The purpose of this study is to describe and formulate an environmental and sustainable shifting cultivation model. The data were collected through field observation and in-depth interview with the informants. Then, the analysis was performed by using Interactive analysis model. Interactive analysis is an interactive and circular method of analysis between data collection, data condensation, data display, conclusion drawing and verification. The result of the study indicates that the Shifting Cultivation System has a positive impact on the soil, agricultural production level, and socio-economic condition of the local community if it applies local wisdom values along with supervision and technical guidance from expert officers of government insitution in its practice. Shifting cultivation can be implemented to achieve environmental and sustainable agriculture system if there is a policy support and local wisdom consideration.